2022
DOI: 10.1155/2022/8701779
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Alternative and High Safety Profile of Acupuncture Plus Chemotherapy for Advanced Gastric Cancer

Abstract: Objective. The aim of this study is to evaluate the safety and tumor marker level changes of acupuncture plus chemotherapy (FOLFOX4) for advanced gastric cancer. Methods. One hundred and twenty patients with advanced gastric cancer who were treated at our hospital between May 2019 and April 2021 were recruited for prospective analysis, and all patients were allocated to the control and experimental groups in a 1 : 1 ratio using the random number table method, with 60 patients in each group. They received eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…75,173 In a clinical trial for advanced gastric cancer, researchers combined AC with chemotherapy, resulting in significantly lower levels of carcinoembryonic antigen, carbohydrate antigen 19-9, and CA72-4 compared to chemotherapy alone. 174…”
Section: Alleviating Chemotherapy-induced Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…75,173 In a clinical trial for advanced gastric cancer, researchers combined AC with chemotherapy, resulting in significantly lower levels of carcinoembryonic antigen, carbohydrate antigen 19-9, and CA72-4 compared to chemotherapy alone. 174…”
Section: Alleviating Chemotherapy-induced Symptomsmentioning
confidence: 99%
“…Clinical trials have indicated that AC may have a protective effect on bone marrow, leading to an increase in white blood cell count in patients undergoing chemotherapy 75,173 . In a clinical trial for advanced gastric cancer, researchers combined AC with chemotherapy, resulting in significantly lower levels of carcinoembryonic antigen, carbohydrate antigen 19‐9, and CA72‐4 compared to chemotherapy alone 174 …”
Section: Clinical Applications Of Acupuncture In Cancer Therapymentioning
confidence: 99%